2020
DOI: 10.1039/d0tb01677b
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and anti-inflammatory ultrahigh molecular weight polyethylene/tea polyphenol blends for artificial joint applications

Abstract: Periprosthetic joint infection (PJI) is one of the main causes for the failure of joint arthroplasty. In view of the limited clinical effect of oral/injectable antibiotics and the drug resistance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The antibacterial effects of CS, Al 3+ , and TP on P-0.2T-0.2C-0.08Al hydrogel were synergistic. The −NH 3+ and Al 3+ can disturb the cell membranes of bacteria via electrostatic adherence and thus interfere with cellular functions. , TP can also directly bind to cell membranes and damage their structures by producing excess intracellular reactive oxygen species. , Besides, studies have demonstrated that the combination of antibacterial agents and metal ions could improve their antibacterial activities . The inhibition zone diameter of P-0.2T-0.2C-0.08Al further proved its exceptional antibacterial activity (Figure c,d and SI Figure S16).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The antibacterial effects of CS, Al 3+ , and TP on P-0.2T-0.2C-0.08Al hydrogel were synergistic. The −NH 3+ and Al 3+ can disturb the cell membranes of bacteria via electrostatic adherence and thus interfere with cellular functions. , TP can also directly bind to cell membranes and damage their structures by producing excess intracellular reactive oxygen species. , Besides, studies have demonstrated that the combination of antibacterial agents and metal ions could improve their antibacterial activities . The inhibition zone diameter of P-0.2T-0.2C-0.08Al further proved its exceptional antibacterial activity (Figure c,d and SI Figure S16).…”
Section: Resultsmentioning
confidence: 84%
“…29,54 TP can also directly bind to cell membranes and damage their structures by producing excess intracellular reactive oxygen species. 55,56 Besides, studies have demonstrated that the combination of antibacterial agents and metal ions could improve their antibacterial activities. 57 The inhibition zone diameter of P-0.2T-0.2C-0.08Al further proved its exceptional antibacterial activity (Figure 4c,d and SI Figure S16).…”
Section: Mechanical Properties Of Hydrogelsmentioning
confidence: 99%
“…On this basis, alginate microgel is prepared to encapsulate GTPs, which could effectively kill S. aureus and promote the proliferation and differentiation of osteoblasts. Ren et al (2020) prepared an ultrahigh molecular weight polyethylene (UHMWPE) implant with strong antibacterial properties by mixing TPs, which greatly reduced periprosthetic joint infection and improved the success rate of joint replacement surgery. Furthermore, it is suggested that TPs blend UHMWPE is expected to become a multi-functional prosthesis for joint replacement to meet the needs of patients.…”
Section: Application In Medicinementioning
confidence: 99%
“…This can be achieved through diverse chemical and enzymatic grafting methods. Commonly used antibacterial chemicals can be classified into several groups, including phenolic compounds (tannic acid, tea polyphenol , ), an N -halamine compound, , and diverse amino compounds such as chitosan, , chitosan oligosaccharides, poly l -lysine, and lactoferrin . These reactive chemicals operate via coupling with the residue groups such as serine, tyrosine, and lysine in silk fibroin chains, endowing SF with outstanding antibacterial effects.…”
Section: Introductionmentioning
confidence: 99%